Extended-Release Guaifenesin/Pseudoephedrine Hydrochloride for Symptom Relief in Support of a Wait-and-See Approach for the Treatment of Acute Upper Respiratory Tract Infections: A Randomized, Double-Blind, Placebo-Controlled Study - Edward J. Septimus, MD, FIDSA, FACP, FSHEA; Helmut H. Albrecht, MD, MS, FFPM; Gail Solomon, MS; Tim Shea, BS; Eric P. Guenin, Pharm.D, Ph.D, MPH (Elsevier, 2017)
Background: Despite the well-known fact that antibiotics (AB) are not effective against viruses, many patients ask for - and all too often doctors provide - AB for treating URTIs. Over-prescribing of AB is one of the key causes for the development of bacterial resistance, which the U.S. Centers for Disease Control and Prevention (CDC) calls "one of the world's most pressing public health problems". In addition to the CDC initiated "Get Smart About Antibiotics" campaign, focused on educating doctors the public about the importance of appropriate AB use, other programs tackling this problem include the development of new treatment paradigms. Data published at the Oregon Health & Science University demonstrated that a 'wait-and-see' approach, without an AB prescription for the treatment of acute childhood ear infections, was as quick, safe, and effective in resolving the infections as an AB prescription (Spiro DM, Tay KY, Arnold DH, Dziura JD, Baker MD, Shapiro ED. Wait-and-See Prescription for the Treatment of Acute Otitis Media. JAMA 2006; 296:1235-1241). Objective: To try and reduce inappropriate prescribing practices, a wait and see or delayed approach requires patients to return for a prescription if their symptoms persist or worsen. The aim of this study was to determine whether treatment with Mucinex D (Reckitt Benckiser LLC, Parsippany, New Jersey) lowers the use of antibiotics in the treatment of URTIs when compared with placebo. Methods: Patients aged 18 to 75 years with symptoms of acute URTIs were randomized to 1200 mg guaifenesin/120 mg pseudoephedrine hydrochloride extended-release, bilayer tablets or matching placebo for 7 consecutive days. Eligible patients met physician's criteria for antibiotic therapy but were considered suitable for a wait and see approach (withholding antibiotics for ≥48 hours). Patients recorded symptom ratings via an interactive voice response system. Results: One thousand one hundred eighty-nine patients enrolled; data are presented for the modified intent-to-treat population (n = 1179). At Day 8, significantly fewer patients receiving guaifenesin/pseudoephedrine versus placebo desired antibiotics (4.2% vs 8.0%). No adverse effects were reported due to patients not taking antibiotics. Significant reductions in URTI symptoms were observed for extended-release guaifenesin/pseudoephedrine versus placebo, from Day 1 throughout the study; however, the proportion of patients experiencing overall relief at the Day 4 evening assessment (primary end point) did not reach statistical significance. Treatment-related adverse events were reported in 9.8% and 4.7% of patients receiving guaifenesin/pseudoephedrine and placebo, respectively. Conclusions: The study found that a wait and see approach was associated with decreased antibiotic use. In addition, the use of a guaifenesin pseudoephedrine combination product provided an effective symptom control compared to a placebo and a well-tolerated first-line strategy for the management of URTIs. This study was not designed to assess the effects of guaifenesin or pseudoephedrine individually. Other limitations include the need for better clinical methods to assess the effectiveness of treatments for acute symptoms of patients with URTIs. ClinicalTrials.gov identifier: NCT01202279.